Sosialisasi dan Edukasi Pembuatan Pewarna Alami Dedaunan Sebagai Pewarna Kain Tenun Sesek Pada Kelompok Pengrajin Tenun Kembang Sukses Desa Kembang Kerang Daya Kecamatan Aikmel Lombok Timur - Muhamad Majdi; Bidarita Widiati; Tina Melinda; Dandi Pramana; Ryan Satria Pribadi (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
In the process of producing sesek woven fabric, many weavers in Kembang Kerang Daya Village still use synthetic (chemical) dyes that can have negative impacts on both environmental and human health. The purpose of this activity is to provide education and socialization to the Kembang Sukses weaving group regarding the production of natural dyes from leaves to help maintain environmental health. The educational and socialization activities were carried out over three days using lecture, discussion, and practical methods. A total of 19 participants from the Kembang Sukses weaving group took part in this activity. The results of this activity showed a significant change in the knowledge level of the Kembang Sukses weavers after receiving education and socialization. This was demonstrated by an increase in the category of products using natural dyes from 0% to 60%, a decrease in the use of synthetic dyes from 100% to 50%, an increase in knowledge about the environmental impacts of synthetic dyes by 20% (from 50% to 70%), and an improvement in the weavers’ ability to produce natural dyes up to 80%. Keywords: syntethetic, natural-dyes-from-leaves, environmental-health